Unusual Scaffold Rearrangement in Polyaromatic Hydrocarbons Driven by Concerted Action of Single Gold Atoms on a Gold Surface. (15th November 2022) - Mendieta‐Moreno, Jesús I.; Mallada, Benjamin; de la Torre, Bruno; Cadart, Timothée; Kotora, Martin; Jelínek, Pavel
Abstract: Chemical transformation of polyaromatic hydrocarbon (PAH) molecules following different reaction strategies has always been the focus of organic synthesis. In this work, we report the synthesis of a PAH molecule, formation of which consists of an unusual C−C bond cleavage accompanied by a complex π‐conjugated molecular scaffold rearrangement. We demonstrate that the complex chemical transformation is steered by concerted motion of individual Au 0 gold atoms on a supporting Au(111) surface. This observation underpins the importance of single‐atom catalysis mediated by adatoms in on‐surface synthesis as well as catalytic activity of single Au 0 atoms facilitating cleavage of covalent carbon bonds. Abstract : The on‐surface synthesis of a polyaromatic hydrocarbon molecule is described. Mechanistically, the synthesis involves an unusual C−C bond cleavage catalyzed by Au adatoms with a molecular scaffold rearrangement. This rearrangement in the π‐conjugated molecular scaffold is possible because of the concerted action of two Au adatoms that catalyze the reaction on the gold surface.